Study writing - Hamp-Lyons, Liz (Cambridge University Press, 1987)
Study Writing is for learners who need to write complete texts in English as part of their studies or work. Part I presents and practises different principles of organising information in writing, such as classifying, defining, and describing sequences and cycles. Each unit focuses on a relevant aspect of grammar and provides learners with a range of comprehension and writing tasks. Part II explores one possible framework for handling complete texts: recognising a situation, defining the problem involved, presenting and evaluating solutions. Study Writing: - adopts an interactive approach emphasising the close relationship between writer and reader; - concentrates on writing as a process, with many opportunities for cooperative work in pairs and small groups; - enables learners to progress from producing short pieces of guided writing to creating longer texts with less guidance; - provides up to 40-60 hours of classwork, with opportunities for further writing as homework; - includes a detailed Teacher's Guide